What shapes community acceptance of large-scale solar farms? A case study of the UK's first 'nationally significant' solar farm. (October 2020) - Roddis, Philippa; Roelich, Katy; Tran, Katherine; Carver, Stephen; Dallimer, Martin; Ziv, Guy
Highlights: Empirical studies of community acceptance of large-scale solar farms are lacking. We present a case study of the UK's first 'nationally significant' solar farm. We identify 28 determinants shaping community acceptance of large-scale solar farms. Key issues are 'green-on-green'; scale; place attachment; policy; process; justice. We also propose a novel 'relational' understanding of community acceptance. Abstract: New renewable energy infrastructure is essential to deliver net zero policies in response to climate change, but a lack of community acceptance is a potential barrier. It is therefore important to understand what shapes community acceptance and identify policy responses. This paper presents a case study of community acceptance of a large-scale solar farm in the UK, the first to be classified as 'nationally significant' infrastructure. In doing so, it provides the first empirical study of community acceptance of a large-scale solar farm in a developed country context, building on existing studies which use hypothetical approaches such as choice experiments, or surveys which measure general attitudes rather than responses to specific developments. The paper uses mixed methods (quantitative content analysis of online comments on the planning proposal; qualitative semi-structured interviews with local residents and key stakeholders; and participant observation) to identify determinants shaping community acceptance of large-scale solar farms. We discover 28 determinants which we group into eight categories: aesthetic, environmental, economic, project details, temporal, social, construction and process. We argue that these findings help to reveal broader issues underlying community acceptance of solar farms and other renewable energy infrastructure: 'green-on-green' tensions; issues of scale and place attachment; policy, process and justice. We also contribute a novel understanding of community acceptance as 'relational', by which we mean it is informed by the deployment of other energy technologies and the wider energy policy landscape, not just the specific project. We conclude with recommendations for how policymakers can respond to the issues identified by this article.